IMPLEMENTASI JARINGAN SYARAF TIRUAN DALAM SISTEM PENDUKUNG KEPUTUSAN (SPK) UNTUK MEMILIH PERGURUAN TINGGI - Yulianti, Liza (UNIVED Press, 2013)
This research is focusing on back-propagation algorithm with neural network that have to be implemented with MATLAB software. The data is observe directly and studying about university election by the graduate high school student. This research wants to find the direct problem, so it can be implemented with neural network by using back-propagation algorithm. This research using three (3) model of neural network back-propagation algorithm. From the data have been analyze with MATLAB software, the training convergence process stop at 5th iteration, last MSE = 1,01777. Meanwhile the testing convergence process stop at 5th iteration, with last MSE = 0,288833.